No time to think : the menace of media speed and the 24-hour news cycle - Rosenberg, Howard, 1938- (Continuum, 2009)
An eviscerating look at the state of journalism in the age of the 24 hour news cycle by a Pulitzer Prize-winning television critic and a veteran news correspondent. No Time To Think focuses on the insidious and increasing portion of the news media that, due to the dangerously extreme speed at which it is produced, is only half thought out, half true, and lazily repeated from anonymous sources interested in selling opinion and wild speculation as news.€ These news item can easily gain exposure today, assuming a life of their own while making a mockery of journalism and creating casualties.